The Relationship Between Energy Consumption and Economic Growth in South and Southeast Asian Countries: A Panel VAR Approach and Causality Analysis - Rezitis, Anthony N.; Ahammad, Shaikh Mostak (International Journal of Energy Economics and Policy, 2015)
This study investigates the dynamic relationship between energy consumption and economic growth in nine South and Southeast Asian countries (i.e., Bangladesh, Brunei Darussalam, India, Indonesia, Malaysia, Pakistan, the Philippines, Sri Lanka, and Thailand) using a panel data framework. The period for the study is 1990–2012, and the World Bank Development Indicators dataset is used. This study applies a panel vector autoregression (VAR) model to provide impulse response functions (IRFs), which enable the impact of shocks to be examined between real gross domestic product (GDP), energy use (ENERGY), real gross fixed capital formation (GFC), and total labor force (LABOR). In addition, panel Granger causality tests are employed to examine the direction of causality between energy consumption and economic growth. The IRFs show that the shocks of all the variables require a long period to reach the long-run equilibrium level and the greatest response of each variable is attributed to its own shock. The panel Granger causality results evidence bidirectional causality effects between energy consumption and economic growth, which supports the feedback hypothesis, meaning that these variables have strong interdependency between each other. Therefore, policy regarding energy consumption should be considered carefully. Keywords: Panel VAR; Panel impulse response functions; Panel Granger causality; SAARC, ASEAN; Energy consumption JEL Classification: C01; C33; O53; Q43